2017
DOI: 10.1371/journal.pone.0168537
|View full text |Cite
|
Sign up to set email alerts
|

Association of CKD-MBD Markers with All-Cause Mortality in Prevalent Hemodialysis Patients: A Cohort Study in Beijing

Abstract: The relationships between all-cause mortality and serum intact parathyroid hormone (iPTH), calcium, and phosphate are fairly diverse in patients on maintenance hemodialysis according to prior studies. This study evaluated the association of chronic kidney disease-mineral and bone disorder (CKD-MBD) markers with all-cause mortality in prevalent hemodialysis patients from 2007 to 2012 in Beijing, China. A cohort, involving 8530 prevalent hemodialysis patients who had undergone a 6–70 months follow-up program (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Hence, CKD‐MBD patients should be educated about their illness, early prevention, multidisciplinary early diagnosis, and treatment plans, thereby improving their quality of life and long‐term survival . We hope this case report will highlight the awareness of nephrologist across the globe apropos such cases and timely therapeutic measures would be taken.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, CKD‐MBD patients should be educated about their illness, early prevention, multidisciplinary early diagnosis, and treatment plans, thereby improving their quality of life and long‐term survival . We hope this case report will highlight the awareness of nephrologist across the globe apropos such cases and timely therapeutic measures would be taken.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have confirmed that hypophosphatemia can increase the all-cause mortality and infectionrelated mortality of hemodialysis patients compared with the range of serum phosphorus recommended by the kidney disease outcomes quality initiative (KDOQI) [16][17][18]. Other studies have found that hypophosphatemiaincreases the mortality of hemodialysis patients over 65 years old [19].…”
Section: Discussionmentioning
confidence: 90%
“…The relationship between serum iPTH level and allcause mortality in dialysis patients is still controversial. Most epidemiologic studies have suggested that the association between iPTH and all-cause mortality in dialysis patients is U-shaped [12][13][14][15]. Some other researches indicate that there is no correlation between serum iPTH level and mortality risk [1,4,16].…”
Section: Discussionmentioning
confidence: 99%